Sử dụng phần mềm NetKGMCschool hỗ trợ tổ chức dạy học thực hành trên máy vi tính trong giáo dục nghề nghiệp - Nguyễn Lê Bảo Khuyên, Nguyễn Lê Bảo Khuyên; Đỗ Thanh Tùng, Đỗ Thanh Tùng (Tạp chí Giáo dục, 2026)
In the context of digital transformation in vocational education, computerbased practical teaching places high demands on interaction, monitoring, and evaluation of the learning process. However, in practice, instructors still face difficulties managing practical classes due to limited monitoring of student progress, slow feedback, and a lack ofsuitable support tools. This paper aims to evaluate the initial effectiveness of NetKgmcSchoolsoftware in supporting the organization of computer-based practical teaching at Kien Giang Medical College.The study uses a descriptive survey design with quantitative analysis, involving 387 students and 20 instructors teaching practical courses at the college. The results show that students are highly satisfied with the software; criteria related to enhanced interaction, monitoring, and feedback during practical sessions ranged from 80% to 95%. The software has now been deployed in 12 educational institutions with a total of 497 computers, supporting instructors in monitoring learning activities, sharing learning materials, and organizing real-time assessments. These results provide initial evidence of the applicability of digital classroom management systems in practical teaching and suggest directions for developing digitized practical teaching models in vocational education.